JAVA SENA (Makanan Ringan) Desa Mandirejo Merakurak - Diah Rachmawati Novida; Rokhadi Rokhadi; Hariyanti Hariyanti; Heri Tugas Setyawati; Sukistanto Sukistanto; L Happy Amira S (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
In the implementation of this KKN, students as activity organizers are required to find problems and potentials that exist in the community. Then, with the abilities they have, students are required to prepare a work program that is able to provide solutions or solve problems and raise potential according to their field of knowledge. Pangklangan Hamlet, Mandirejo Village, Merak Urak District is the location designated as the location for the Independent KKN of the Muhammadiyah Tuban College of Economics for the 2022-2023 Academic Year.